Association between migraine severity and sleep quality: a nationwide cross-sectional study - Nura A. Almansour; Nura A. Almansour; Seham S. Alsalamah; Seham S. Alsalamah; Razan S. Alsubaie; Razan S. Alsubaie; Nada N. Alshathri; Nada N. Alshathri; Yasmeen A. Alhedyan; Yasmeen A. Alhedyan; Faisal Y. Althekair’s; Faisal Y. Althekair’s; et al. (Frontiers in Neurology)
BackgroundMigraine is a primary headache disorder that affects more than 1 billion individuals globally and imposes a significant disability burden on society. Although migraine patients commonly experience poor sleep quality, the relationship between migraine and sleep is not yet fully understood. This study therefore aimed to determine the association between sleep quality and migraine severity.MethodsA comparative cross-sectional study was conducted with 1,399 participants across all regions of Saudi Arabia from August to October 2023 using standardized questionnaires. Participants were categorized into patients with migraine and non-migraine patients, according to the International Headache Society (IHS) criteria. This study utilized The Migraine Disability Assessment Scale (MIDAS) and Pittsburgh Sleep Quality Index (PSQI) to evaluate migraine severity and sleep quality, respectively.ResultsThe prevalence of migraine was 25%, while poor sleep quality was evident in 42.4% of the patients. No significant difference in PSQI scores was observed between patients with migraine and non-migraine patients (p = 0.821). Migraine patients with poor sleep quality showed significantly higher MIDAS scores than those with good sleep quality (10.37 vs. 6.58; p = 0.002), while patients with migraine with higher levels of disability had higher PSQI scores than those with lower levels of disability, although the difference was not statistically significance (7.61 vs. 6.81, p = 0.053). A significant positive correlation was found between the PSQI and MIDAS scores (r = 0.179, p < 0.001). MIDAS was also significantly positively correlated with the following PSQI components: subjective sleep quality (p = 0.047), sleep latency (p < 0.001), sleep disturbance (p < 0.001), and daytime dysfunction (p < 0.001).ConclusionThese findings suggest a notable correlation between poor sleep quality and increased migraine severity, emphasizing the importance of addressing sleep disturbance as a potential strategy to mitigate migraine severity and improve patient outcomes.